2006
DOI: 10.53841/bpssepr.2006.2.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Group versus individual approach? A meta-analysis of the effectiveness of interventions to promote physical activity

Abstract: The purpose of the study was to conduct a meta-analysis to empirically compare the relative merits of different contexts typically employed in the physical activity intervention literature for five categories of outcomes: adherence, social interaction, quality of life, physiological effectiveness, and functional effectiveness. Four contexts were examined: home-based programmes not involving contact from researchers or health-care professionals, home-based programmes that involved some contact, standard exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(63 citation statements)
references
References 68 publications
2
55
1
5
Order By: Relevance
“…40 For example, social support provided in group training from trainers and other exercise participants may increase program adherence, quality of life, and social interaction. 41 Program adherence (43%) was found to be lower than previous studies involving firefighters (50%-83%). 6 Reasons for low participant were also observed, aligning with previous exercise interventions in firefighters (see Andrews, Gallagher 6 for review).…”
Section: Continuation Of Specialised Programscontrasting
confidence: 55%
See 1 more Smart Citation
“…40 For example, social support provided in group training from trainers and other exercise participants may increase program adherence, quality of life, and social interaction. 41 Program adherence (43%) was found to be lower than previous studies involving firefighters (50%-83%). 6 Reasons for low participant were also observed, aligning with previous exercise interventions in firefighters (see Andrews, Gallagher 6 for review).…”
Section: Continuation Of Specialised Programscontrasting
confidence: 55%
“…These qualitative assessments support the feasibility of the intervention and have been previously utilised in effective interventions for firefighters 6 as well as healthy adult populations 40 . For example, social support provided in group training from trainers and other exercise participants may increase program adherence, quality of life, and social interaction 41 …”
Section: Discussionmentioning
confidence: 73%
“…Previous reviews have found negligible to small effects for distance-based PA behavior change interventions that have relied on print and telephone modes of intervention delivery among cancer survivors (44). Furthermore, group-based strategies are effective for increasing PA behavior for most populations and in most settings, and may be more efficacious than individually delivered programs when the appropriate group dynamic principles are used (32,45,46). Despite being the most effective approach for PA behavior change compared with mediated delivery (e.g., email or telephone; ref, 47), only one study used face-toface and group-based delivery, but was not an RCT and thus excluded from the meta-analysis (42).…”
Section: Discussionmentioning
confidence: 99%
“…At long-term care facilities, exercise programs with older adults are often delivered in group-based or individual-based settings [68]. The participants in the study were organized randomly into one-on-one or group-based exercise sessions with the robot.…”
Section: Experimental Designmentioning
confidence: 99%